Corporate Social Responsibility: Contributions of Father Alberto Hurtado in Chile [la Responsabilidad Social Empresarial: Aportes del Padre Alberto Hurtado en Chile] - Caiceo-Escudero, J (FahrenHouse, 2019)
Since the middle of the last century began coining the concept of Corporate Social Responsibility, which has gradually been specifying and introducing the new needs and problems of today s changing society. However, in 1947, Father Alberto Hurtado founded Association Trade Union Chile -ASICH- with the intention of forming future trade union leaders in the country with a social thought Christian, inspired by the Social Doctrine of the Catholic Church; there not only were given the principles of trade unionism but that the elements that companies should have to be fair to its employees; in the background, they were laying the foundations of corporate social responsibility. In the light of the above, the objective of this work is to provide Christian view that has taken Corporate Social Responsibility in Chile. © 2019 FahrenHouse. All rights reserved.